2007
DOI: 10.1521/suli.2007.37.3.322
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Crisis Hotline Outcomes Part 1: Nonsuicidal Crisis Callers

Abstract: The effectiveness of telephone crisis services/hotlines, examining proximal outcomes as measured by changes in callers' crisis state from the beginning to the end of their calls to eight centers in the U.S. and intermediate outcomes within 3 weeks of their calls, was evaluated. Between March 2003 and July 2004, 1,617 crisis callers were assessed during their calls and 801 (49.5%) participated in the followup assessment. Significant decreases in callers' crisis states and hopelessness were found during the cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(156 citation statements)
references
References 26 publications
6
144
0
3
Order By: Relevance
“…Thus 21 articles met the inclusion criteria, see Tables 1-3. The 21 articles represented 19 separate studies as Gould et al 16 and Kalafat et al 17 reported on an evaluation of crisis helpline outcomes at eight sites in the US; and Farberow et al 18 and Litman et al 13 presented findings on a study of frequent callers to a Los Angeles crisis helpline. In the 21 articles included in this review, callers who made multiple calls to crisis helplines were referred to as frequent, chronic or repeat callers.…”
Section: Resultsmentioning
confidence: 99%
“…Thus 21 articles met the inclusion criteria, see Tables 1-3. The 21 articles represented 19 separate studies as Gould et al 16 and Kalafat et al 17 reported on an evaluation of crisis helpline outcomes at eight sites in the US; and Farberow et al 18 and Litman et al 13 presented findings on a study of frequent callers to a Los Angeles crisis helpline. In the 21 articles included in this review, callers who made multiple calls to crisis helplines were referred to as frequent, chronic or repeat callers.…”
Section: Resultsmentioning
confidence: 99%
“…Only the caller has the authority and responsibility to make decisions about his own life, including the judgement that his best interests are to end it. Unlike many suicide crisis helplines (de Anda and Smith 1993;Mishara 1997;King et al 2003;Barber et al 2004;Kalafat et al 2007;Ingram et al 2008), Samaritans will not advise or actively intervene to deflect a caller who declares intent to die by suicide. Volunteers aim to offer the caller unconditional, nonjudgemental acceptance and support.…”
Section: Introductionmentioning
confidence: 99%
“…Selon Mishara et Giroux (1993), ce sont surtout sur ces impacts que les écoutants doivent se centrer afin d'éviter le découragement puisqu'ils ne pourront régler les problèmes d'une vie en un seul appel, particulièrement en ce qui concerne les appelants réguliers. Kalafat et al (2007) isolées ou qui n'ont pas les moyens financiers nécessaires pour faire appel à des professionnels. Ils peuvent aussi être utilisés comme complément à la thérapie afin de permettre un soutien additionnel.…”
Section: Les Centres D'écoute Ou D'intervention Téléphoniqueunclassified
“…Une plus grande proportion de ces appelants est déprimée et ils sont deux fois plus nombreux que les appelants occasionnels à avoir tenté de se suicider (Gréer, 1976 ;Haywood, 1981). À ce sujet, Kalafat et al (2007) (Bartholomew & Olijnyk, 1973 ;Haywood, 1981 ;Leuthe & O'Connor, 1981 ;Sawyer & Jameton, 1979). Il existe donc un danger réel à sous-estimer la souffrance des appelants réguliers.…”
Section: Les Principales Caractéristiques Des Appelants Réguliersunclassified
See 1 more Smart Citation